Begonia sakaiana Begoniaceae (sect. Petermannia) a new species from Sarawak, Borneo - Meekiong, Kalu; Stephen Teo, Ping (Suriana Botanic Conservation Gardens (SBCG), 2025)
Begonia sakaiana Meekiong & S.P.Teo, a new Begonia species from Gunung Sejanjang, Kuching, Sarawak is described and illustrated herein. The new species is a cane-liked Begonia from section Petermannia, similar to B. sarangica Kiew & S.Julia, but differs by morphologies.